PENGARUH INTENSITAS PENGGUNAAN MEDIA SOSIAL INSTAGRAM TERHADAP AKHLAK PESERTA DIDIK - Desi Rahmatiwi; Joko Sarjono; Muhammad Fatchurrohman (Al'Ulum Jurnal Pendidikan Islam, 2022)
This study aims to determine the influence of the intensity of instagram social media use on the morals of students. This type of research is quantitative research with research subjects at SMA Negeri 2 Sukoharjo. The independent variable (Variable X) of this study is the intensity of instagram social media use, while the dependent variable (Variable Y) is the morals of the learners. The study population was 945 respondents and a sample of 90 people. In collecting data, researchers used an instrument in the form of a questionnaire consisting of 40 question items and distributed to respondents using a google form, testing the validity of the research instrument using the Aiken Validity Test and testing its reliability using the Spearman Brown Test. The scoring of question items in the questionnaire uses a likert scale of 1-4 to determine the level of intensistas of instagram social media use and student morals. The results showed that the intensity of students' Instagram social media use was high with a percentage of 52.2%. The results of the hypothesis test using a simple linear regression technique obtain a signification value smaller than the probability value (0.019 < 0.05) then the regression model can be used to predict the participation variable, the regression equation obtained is Y = 54.609 + 0.148X. and based on the value of t, it is known that the calculation is 2.381 > ttabel 1.991, so it can be concluded that variable X affects variable Y. The use of Instagram social media affects the morals of students both to positive and negative things, where the level of intensity of social media use will affect the moral and moral development of students in daily life both in terms of morals to God, morals to humans, and morals towards the environment.